Making and selling cars : innovation and change in the U.S. automotive industry - Rubenstein, James M. (Johns Hopkins University Press, 2001)
The automobile has shaped nearly every aspect of modern American life. This text documents the story of the automotive industry, which, despite its power, is constantly struggling to assure its success.